The pertinent role of forest inventory in making choice of silvicultural operations in community forests of Nepal - Baral, S. G.; Vacik, H.; Chhetri, B. B. K.; Gauli, K. (Banko Janakari, 2018)
This paper explores the application of forest inventory to design silvicultural operations and its implementation to community forests. Four-time series forest inventory data (2005, 2010, 2013 and 2016) of Terai community forests were analysed, focusing on the type and size of tree removals from the forests. In addition, content analysis of the management plans of the forests was carried out and consultations were held with key informants. Though the forest inventory was prepared during the preparation of management plans, the results did not provide proper guidance on the selection of silvicultural operations, which were decided without a clear definition of the management objectives. They were very generic and largely ignored site-specific forest stand conditions. Most commonly practised silvicultural operations were cleaning and selective harvesting, which were similar for all forest blocks, though they varied in respect of forest stand conditions. The time series analysis of the inventory data showed that pole-sized trees were consistently removed in all four periods and emphasis was on extracting good quality trees without considering its effects on the stand. The study concludes that the current forest inventory is not very relevant in making a choice about silvicultural operations and the current practices might cause economic and ecological losses. Hence, we argued for identifying minimum forest management requirement necessary for the sustainable forest management that the silvicultural operations should be decided based on the management objectives and conditions of the forest, considering the ecological and economic value of the forest. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 65-75